Frequency of peripheral neuropathy in pre diabetics in sub Himalayan region: a cross sectional observational study - Lal, Roshan; Kaushik, Madan; Sharma, Sudhir; Raina, Rajiv; Mahajan, Sanjay; Chaudhary, Satish; Sharma, Ritin; Kanwar, Neeraj; Thakur, Manish Kumar (International Journal of Research in Medical Sciences, 2018)
Background: Peripheral neuropathy in pre diabetics has been studied in various studies till now. Many are in support and many against. No data was available in any study using all three criteria i.e. impaired fasting glucose, impaired glucose tolerance and HbA1C. Aim was to study the frequency of peripheral neuropathy in pre diabetics in a tertiary health care centre in sub Himalayan region. Methods: A 50 patients of prediabetes were enrolled for this study; preformed proforma was used to collect the information, data on examination and investigations. Then these patients were subjected to nerve conduction studies. Results: Out of total 50 pre diabetic patients 9(18%) were diagnosed having peripheral neuropathy. Maximum number of pre diabetic patients were (26) in the age group 46-55 years with mean age of 44.49 years ±7.01 (S.D.). 28 (56%) were males with a female to male ratio of 1:1.27. 20% patients had complaint of polyuria, 12% presented with polydipsia, 14% of total pre diabetic patients had paresthesia on history. 6% patients had impaired vibration and position sense on clinical examination. Out of total 9 patients having evidence of Peripheral Neuropathy 6 (66.66%) were meeting all three criteria for Prediabetes while 8 (88.88%) had IFG, 7 patients had IGT. 42% of the patients were fulfilling the criteria of metabolic syndrome. 28 had raised TGs and out of them 5 (17.8%) had peripheral neuropathy. Out of 24 obese patients, 4 (16.6%) had peripheral neuropathy. Out of 9 patients with peripheral neuropathy 66.66% patients were considered to be suffering with peripheral neuropathy on the basis of sensory symptoms and 33.33% were considered on the basis of impaired vibration and position sense on examination, one patient diagnosed on the basis of nerve conduction studies. 38% were in high risk group of developing T2DM in future as per Indian diabetes risk score. Mean compound motor action potential (CMAP) and nerve conduction velocity (NCV) were less in patients with peripheral neuropathy in comparison to patients without peripheral neuropathy. Conclusions: Peripheral neuropathy can occur in prediabetes though it is difficult to confirm it. Most common is small fiber neuropathy which can be diagnosed on the basis of history and examination. But by diagnosing it early in the course of prediabetes, morbidity and mortality secondary to neuropathy can be prevented.